Arthur rocks with Binky - Krensky, Stephen; Willard, Sandra (Boston : Little, Brown, 1998)
Arthur attends a rock concert in hopes of meeting the famous musical group, Binky.
"Based on the teleplay by Sandra Willard."
"RL: 3.8"--P. [4] of cover.
3 6 7 9 13 15 19 21 23 31 33 34 36 38 39
Keywords: Rock music -- Fiction; Aardvark -- Fiction; Animals -- Fiction; Aardvark -- Fiction; Animals -- Fiction; Rock groups -- Fiction; Arthur (Fictitious character : Brown) -- Fiction